Identification of UDP-Glucuronosyltransferase mRNA in human platelets: differential levels in smokers and non-smokers - Yazun Jarrar; Mansour Almansour; Dina Abulebdeh; Wesam Nasser; Qais Jarrar; Sara Abudahab; Su-Jun Lee (Platelets, 2025)
Background UDP-glucuronosyl transferases (UGTs) are major enzymes of phase II drug metabolism, yet their expression in human platelets remains underexplored. Objectives: This study aimed to characterize the mRNA expression profile of UGT isoforms in human platelets and to assess differences between cigarette smokers and nonsmokers.Methods Total RNA was extracted from platelet-rich plasma (PRP), buffy coat (BC), and liver samples. After reverse transcription, PCR was performed to detect UGT isoforms including UGT1A1, 1A3, 1A4, 1A5, 1A6, 1A7, 1A8, 1A9, 1A10, 2B7, and 2B15. The mRNA levels of UGT1A5 and 2B15 in PRP were quantified and compared to levels in liver and BC. PRP samples from smokers and nonsmokers were also analyzed.Results UGT1A5 and 2B15 mRNAs were detected in human platelets. UGT1A5 expression was significantly higher in PRP than in liver, while it was about threefold lower. Both genes showed elevated expression in smokers’ platelets, approximately 11.3-fold for UGT1A5 and 3.3-fold for UGT2B15, compared to nonsmokers.Conclusions This study concludes the presence of UGT1A5 and 2B15 mRNA in human platelets and their elevated level in the platelets of smokers. Further research, including pharmacokinetic studies and protein-level validation, is needed to understand their functional significance.